The Impact of Omega-3 Fatty Acids on the Onset and Management of Alzheimer’s Disease - Biskup, Marta; Bartoszek, Aleksandra; Kopeć, Karolina; Marut, Agnieszka; Misiuk, Jagoda; Adamiuk, Julia; Skuba, Adriana; Załuska, Katarzyna; Świdniak, Agnieszka; Nykiel, Sylwia (Quality in Sport, 2025)
Introduction and Purpose: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, whose etiology remains complex. Research suggests that dietary factors, particularly omega-3 fatty acids, may play a role in modulating neuroinflammation and amyloid-beta pathology—key hallmarks of AD. Omega-3 acids have been linked to improved neuronal function and reduced cognitive decline in aging populations. This review explores their impact on the progression and management of Alzheimer’s disease. Materials and Methods: This article is a comprehensive review based on articles obtained from scientific databases like PubMed, selected for their importance to the subject. Results: The relationship between omega-3 fatty acids and cognitive impairment, including Alzheimer’s disease, has been widely studied. Research suggests that docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) may support brain health by reducing neuroinflammation, enhancing synaptic function, and potentially slowing cognitive decline. Although some studies show cognitive benefits, others report mixed results due to variationsin dosage, duration, and patient characteristics. While omega-3s are not a cure, their neuroprotective potential underscores the need for further research to optimize their clinical application. Conclusion: Although research indicates possible cognitive benefits, particularly in early Alzheimer’s disease or mild cognitive impairment, findings remain inconsistent. While omega-3s are not a definitive treatment, their neuroprotective properties highlight the need for further scientific investigation in the field. Future research is required to determine the optimal dosage of omega-3 fatty acids and to identify patient-specific factors that influence their therapeutic efficacy.